RECORDS OF GOOSE BARNACLES (CIRRIPEDIA, LEPADIDAE) IN THE NORTHEAST BRAZILIAN REGION - Farrapeira, Cristiane Maria Rocha (Revista Nordestina de Zoologia, 2010)
The goose barnacles are exclusively marine, with worldwide distribution in the warm temperate and tropical seas and known for its usual settlement on living organisms and artificial floating substrata conducted by sea currents. This paper reports lepadis barnacles listed in inventories carried out by several authors and collected from the northeastern coast of Brazil (only Rio Grande do Norte and Pernambuco states), including the Saint Peter and Saint Paul and Fernando de Noronha archipelagos. The samples were collected by hand and using spatula from diverse substrata drifted ashore and on hull of vessels moored in the harbor areas. The specimens had been fixed in alcohol 70%. From the literature review, the vectors of dispersal of these species were considered as shipping, rafting, and phoresy. Five species of lepadids were found: Conchoderma auritum, C. virgatum, Lepas anatifera, L. anserifera, L. hillii, and L. pectinata. All species treated in this study have been cited for the three vectors of dispersal. The first occurrence of Lepas anatifera, L. anserifera, and L. hillii for the Saint Peter and Saint Paul Archipelago was recorded, as well as L. anserifera for the Fernando de Noronha Archipelago and Rio Grande do Norte State. All these new records are linked by shipping routes of the fishing boats among the sites mentioned.